The Nexus between CSR Disclosure and Financial Performance: A Study on Islamic Sharia-based Banking Companies in Bangladesh (Global Journal of Management and Business Research, 2019)
Purpose: The purpose of this study is to investigate the relationship between CSR disclosure and financial performance of listed Islamic Sharia-based banking companies in Bangladesh. Methodology: In this study, Islamic Sharia-based banking companies listed on Dhaka Stock Exchange in Bangladesh is selected. Four listed Islamic Sharia-based banks (66.67%) among six listed banks are taken as sample randomly for this study. Content analysis is used to measure the extent of CSR disclosure of sample banks. A CSR checklist covering sixteen themes with eighty-five items is prepared and a period of 5 years ranges from 2011-2015 is taken for this study. Three accounting based financial performance indicators are used in this study such as return on assets, return on equity and earnings per share. Ordinary least square regression models and Panel data regression models (Fixed effects model or Random effects model) are used to analyze data. The Bruachpagan multiplier test and Hausman specification test have been conducted to employ appropriate model for data analysis.
Keywords: CSR Disclosure; Financial Performance; Listing Age; Independent Director; Size; Islamic Shariabased banks; Bangladesh